Monoclonal Antibodies: Mechanismo of action - Saldarriaga-Valiente, Tatiana (2021)
Monoclonal antibodies exert their activities in a diverse and varied way depending on the targets affected, whether they are tumors, cytokines, viruses, growth factors. There are different mechanisms of action by which monoclonal antibodies can destroy cancer cells: attacking the tumor cell survival cascade, inhibiting tumor growth, interfering with tumor angiogenesis, bypassing programmed cell death and bypassing immune checkpoints. These effects can be carried out by different mechanisms: direct death of tumor cells or death mediated by immune mechanisms.